Beautiful redemption - McGuire, Jamie ([Place of publication not identifed] : [publisher not identified], 2015)
FBI Special Agent in Charge Thomas Maddox and FBI agent Liis Lindy go undercover to spare Thomas' brother Travis Maddox from a prison term by recruiting him into the FBI, but Liis wonders if her feelings for Thomas are more than just a cover story.
Chapter One -- Chapter Two -- Chapter Three -- Chapter Four -- Chapter Five -- Chapter Six -- Chapter Seven -- Chapter Eight -- Chapter Nine -- Chapter Ten -- Chapter Eleven -- Chapter Twelve -- Chapter Thirteen -- Chapter Fourteen -- Chapter Fifteen -- Chapter Sixteen -- Chapter Seventeen -- Chapter Eighteen -- Chapter Nineteen -- Chapter Twenty -- Chapter Twenty-One -- Chapter Twenty-Two -- Chapter Twenty-Three -- Chapter Twenty-Four.
Beautiful redemption /, Beautiful
Keywords: ROMANCE FICTION